2017
DOI: 10.1371/journal.pone.0187696
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microalgae on intestinal inflammation triggered by soybean meal and bacterial infection in zebrafish

Abstract: Soybean meal has been used in many commercial diets for farm fish; despite this component inducing intestinal inflammation. On the other hand, microalgae have increasingly been used as dietary supplements in fish feed. Nevertheless, the vast quantity of microalgae species means that many remain under- or unstudied, thus limiting wide scale commercial application. In this work, we evaluated the effects to zebrafish (Danio rerio) of including Tetraselmis sp (Ts); Phaeodactylum tricornutum (Pt); Chlorella sp (Ch)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…The intestinal epithelial cells act as a first line of defense against potentially harmful agents, while also ensuring the adequate nutrient utilization, immune defense, and growth of fish [69]. The absence of significant difference (p > 0.05) in the intestinal morphology between the fish fed the CON and SUP diets indicated that the presence of the microalga in the digestive tract and the modulation of the gut microbiota caused by it was not enough to modify the structure and integrity of the intestinal villi, which eliminates the possibility of enteritis processes caused by algae.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal epithelial cells act as a first line of defense against potentially harmful agents, while also ensuring the adequate nutrient utilization, immune defense, and growth of fish [69]. The absence of significant difference (p > 0.05) in the intestinal morphology between the fish fed the CON and SUP diets indicated that the presence of the microalga in the digestive tract and the modulation of the gut microbiota caused by it was not enough to modify the structure and integrity of the intestinal villi, which eliminates the possibility of enteritis processes caused by algae.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous strategies have been deployed to mitigate soybean-induced inflammation in fish. These include the supplementation of glutamine, arginine, resveratrol, microalgae, bacteria grown on natural gas and lactoferrin in the feed [ 40 , 41 , 42 , 43 , 44 ]. Fermentation of soybean meal prior to feeding has also been tested in turbot with encouraging results, suppressing the intestinal inflammation and enhancing the intestinal integrity [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…When focusing on long-term effects, the early stage feeding of soybean meal or soy protein was found to have programming effects on inflammation at the juvenile stage (Perera and Yufera, 2016 ). Since soybean meal is an important commercial food source for fish, studies have been done to identify additives for compensating its pro-inflammatory effects and a few candidates were shown to inhibit soybean meal-triggered intestinal inflammation, including lactoferrin (Ulloa et al, 2016 ), microalgae (Bravo-Tello et al, 2017 ), aloe vera (Fehrmann-Cartes et al, 2019 ), the typical cholinesterase inhibitor galantamine (Wu et al, 2020 ), and a phytase-producing strain of Bacillus subtilis (Santos et al, 2019 ).…”
Section: Inflammatory Disease Models In Zebrafishmentioning
confidence: 99%